Lire les histoires sentimentales selon R. Rorty afin de sortir du relativisme culturel (?) - Rutsch, Jan (Verbum – Analecta Neolatina, 2025)
The question of moral and cultural relativism is not only one of the fundamental academic problems but also one of our everyday lives. However, during the twentieth century, ethics was relegated to the realm of art, especially by analytic philosophy, represented in the interwar period by the so-called Vienna Circle. However, using the example of the post-analytic philosopher Richard Rorty and his concept of sentimental stories which aim to increase our capacity for empathy, it seems that art can contribute to a tolerant and respectful human community. Although the types of perception of these stories may vary, according to Maryane Wolf’s conclusions supported by neurocognitive science, it is reading, specifically deep-reading, that can affect our capacity for empathy. In other words, literature can change the world and perhaps, therefore, free us from the grip of cultural relativism.